2007
DOI: 10.2217/14796708.2.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Bifeprunox: A Novel Antipsychotic Agent with Partial Agonist Properties at Dopamine D2 and Serotonin 5-HT 1A Receptors

Abstract: Most second-generation, atypical, dopamine (DA) D2/5-HT2 blocking antipsychotics still induce extrapyramidal side effects (EPS) in higher doses. Weight gain and metabolic disturbances are also a problem, and negative and cognitive symptoms have not been sufficiently addressed. The current brain DA mesolimbic hyperactive/mesocortical hypoactive hypothesis of schizophrenia suggests that DA D2/5-HT 1A receptor partial agonist properties may be more efficacious with less side effects. DA D2 receptor partial agonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 64 publications
(54 reference statements)
1
24
0
Order By: Relevance
“…A 0.75 mg/kg aripiprazole dosage in rats is equivalent to ~7.5 mg in humans (60 kg body weight), while 0.8 mg/kg bifeprunox and 0.1 mg/kg haloperidol is equivalent to ~8 mg and ~1 mg respectively, all of which are within the used/recommended clinical dosages (Casey et al, 2008, Emsley, 2009, Mace and Taylor, 2009. It was reported that aripiprazole and bifeprunox, at these dosages, had over 90% D 2 receptor occupancy in rat brains (Wadenberg, 2007), while haloperidol reached approximately 70% D 2 R occupancy , Naiker et al, 2006, Natesan et al, 2006. Furthermore, the dosages used in this study have been shown to be physiologically and behaviourally effective in rodents (Assie et al, 2006, De Santis et al, 2014, Han et al, 2009, Kesby et al, 2006, Wadenberg, 2007, whilst not causing EPS side-effects (Natesan et al, 2006, Wadenberg, 2007.…”
Section: Animals and Drug Administrationsupporting
confidence: 48%
See 1 more Smart Citation
“…A 0.75 mg/kg aripiprazole dosage in rats is equivalent to ~7.5 mg in humans (60 kg body weight), while 0.8 mg/kg bifeprunox and 0.1 mg/kg haloperidol is equivalent to ~8 mg and ~1 mg respectively, all of which are within the used/recommended clinical dosages (Casey et al, 2008, Emsley, 2009, Mace and Taylor, 2009. It was reported that aripiprazole and bifeprunox, at these dosages, had over 90% D 2 receptor occupancy in rat brains (Wadenberg, 2007), while haloperidol reached approximately 70% D 2 R occupancy , Naiker et al, 2006, Natesan et al, 2006. Furthermore, the dosages used in this study have been shown to be physiologically and behaviourally effective in rodents (Assie et al, 2006, De Santis et al, 2014, Han et al, 2009, Kesby et al, 2006, Wadenberg, 2007, whilst not causing EPS side-effects (Natesan et al, 2006, Wadenberg, 2007.…”
Section: Animals and Drug Administrationsupporting
confidence: 48%
“…It was reported that aripiprazole and bifeprunox, at these dosages, had over 90% D 2 receptor occupancy in rat brains (Wadenberg, 2007), while haloperidol reached approximately 70% D 2 R occupancy , Naiker et al, 2006, Natesan et al, 2006. Furthermore, the dosages used in this study have been shown to be physiologically and behaviourally effective in rodents (Assie et al, 2006, De Santis et al, 2014, Han et al, 2009, Kesby et al, 2006, Wadenberg, 2007, whilst not causing EPS side-effects (Natesan et al, 2006, Wadenberg, 2007. After 1-week administration, all rats were sacrificed between 10:00 AM and 12:00 PM to minimise possible circadian-induced variation of protein expression.…”
Section: Animals and Drug Administrationmentioning
confidence: 90%
“…Since the introduction of aripiprazole in 2002 and then paliperidone, iloperidone, asenapine, and lurasidone, there has been a relative hiatus in the development of new atypical antipsychotic drugs. From the chemical point of view, the new antidepressants and atypical antipsychotics are based around arylpiperazine or arylpiperidine core structures, which may explain their interaction with a large number of G-protein coupled receptors (Rs), including 5-HT 1A , 5-HT 2A , 5-HT 6 , 5-HT 7 as well as D 2 , D 3 , and D 4 receptors. Clues from the clinic that atypical antipsychotics agents can be used as augmentation therapy in patients with poor responses to antidepressants led to the creation of the multitarget strategy for development of CNS active drugs.…”
Section: Introductionmentioning
confidence: 99%
“…1), a potential atypical antipsychotic with reduced extrapyramidal side effects [6]. The structure-activity relationships in the group of 1-aryl-4-(phenylarylmethyl)piperazines [7] led to obtaining SLV 313 (adoprazine) (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation